Avaliação da retração autógena em concretos de alto desempenho com diferentes adições - Ludmila Rodrigues Costa (2008)
High performance concrete is commonly useful by its performance, strength, durability, workability and others. Autogenous shrinkage can be considering one of the reasons of cracks on high performance concretes at early ages. The concrete shrinkage can be influenced by different reasons: piece measurements, water content of mashing, dosage of cement, inert nature, grain size, cure, relative humidity, cements compounds, etc. Detailed studies and experiments carefully done were very important in this paper, which had as objective to study and evaluate the autogenous shrinkages on high performance concrete. And this was function, mainly by kind, content and binary and ternary mixes of different admixtures (blast furnace slag, metacaulim and silica fume), using a superplasticizing of new generation. Other tests were used to evaluate of these concretes with admixtures: compressive strength, tensile strength by diametrical compressive, dynamic modulus of elasticity, absorption (by capillarity and immersion), abrasion and ultrasonography. The concrete with silica fume and blast furnace slag if compared with the others concretes had the best performance because of small shrinkage, good strength and little cement.